Carbon accumulation patterns in soils of tropical peatlands from alluvial origin (Caquetá, Colombia) (2018)
The continuous and dense vegetation of tropical rainforests makes them an important global carbon reservoir. Within the tropical forests, peatlands are important because they stored high contents of organic matter in the soil with several meters deep and low decomposition rates. The spatial distribution, functioning and carbon storage patterns of peatland ecosystems in the Amazon basin remain to be explored. The main objective of this research was to identify the processes that control the accumulation of organic matter (carbon) and the formation of peat in the 8 peatlands located along the Orteguaza River from the Andes foothills to its end at the Caquetá River in the Colombian Amazon. I found that the carbon content of peatland soils was between 0,003 gC cm-2 and 0,009 gC cm-2, dry bulk density was between 0,01 gC cm-3 and 1,7 gC cm-3, total carbon content was between 353 tonC ha and 968 tonC ha. The peatland initiation age using soil radiocarbon was of 1770 ybp. Macrofossil analyses indicated a change from floating vegetation to M. flexuosa dominated swamp forests as the wetland develops into a more autogenic (peat forming) ecosystem. CCA analyses indicated that vegetation was related more with distance of the wetland to the main river channel than to water chemistry. Peat soils were common downstream and almost absent upstream near the Andes. The most likely explanation for the change in carbon content is the change in conditions influenced by the geomorphological development of the river and time since the abandonment of meanders, arms and channels